An evaluation of the impact of PROGRESA cash payments on private inter-household transfers: final report - Teruel, Graciela; Davis, Benjamin (International Food Policy Research Institute, 2000)
One important goal of PROGRESA is to raise the real income of program beneficiaries. At first sight, it is reasonable to assume that any government social program that gives monetary transfers to poor families has a positive effect in raising their income. However, the subsidy can modify the behavior of individuals and thus may cause a change in informal pre-existing private transfers among families as a consequence of increased incomes.In this report we use data from the PROGRESA evaluation datasets to assess the link between the PROGRESA subsidy and private transfers, both monetary and non-monetary. Two methods of empirical analysis are employed. First we use descriptive statistics to compare the frequency and level of inter-household transfers between control and treatment groups at two points in time for which data are available—October, 1998 and November, 1999. We also compare the characteristics of households that receive (or proportion) transfers, and those that do not. Second, we analyze econometrically whether selection into PROGRESA has a significant impact on the incidence and levels of private transfers among households.